Planning to Meet Challenges in Shrinking Rural Regions : Towards Innovative Approaches to Local Planning - Hagen, Aksel; Higdem, Ulla; Overvåg, Kjell (AESOP, 2022)
Norway’s population is increasing, but rural municipalities all over Norway are undergoing depopulation. Of the most sparsely populated municipalities, 75% have had shrinking populations in the last 20 years, often with residents scattered over a large area. In the year of 2019, 71% of all Norwegian municipalities experienced a decline. These demographic developments are expected to continue in the coming decades (NOU 2020:15). Although policy-making and planning have long focused on counteracting these demographic trends, governmental studies show that only massive immigration or a sharp increase in fertility rates can alter this course (NOU 2020:15). For most municipalities, the likelihood of a reversal is very low, both currently and in the near future. In Innlandet, which is the Norwegian case studied in this paper, 31 of 46 municipalities have had a population decline in the last 30 years (in the period 1991-2021), meaning that they have a lower population number in 2021 than in 1991. The decline varies considerably, from -30 to -1% (see table 1). Some municipalities, especially in the eastern and northern part of Innlandet (figure 3), have had an almost continually decline year by year, while others have years in between with small increase in population numbers. The yearly fluctuations in population development are quite strongly influenced by immigration of refugees to Norway, while the natural population change (births, deaths) has a more stable and declining development trend. The decline in population numbers is in the long run expected to continue. The age composition has changed and will keep changing to a significantly older population. This situation has recently been discussed in the demography committee’s report (NOU, 2020: 15). They argue that the political goals for the districts should not be growth, but to create good communities for those who live and/or run a business there.
Keywords: Norway; depopulation; demography; policy-making; planning; Innlandet